Optimizing Digital Marketing Strategy to Boost Sambal Bu Sandra Sales on the Shopee E-commerce Platform - Andini, Ayu; Widyawati, Sri; Setyadi, Taufik (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2025)
Chili is a strategic agribusiness commodity in Indonesia with high economic value, mainly processed products such as chili sauce. Sambal Bu Sandra is a micro-entrepreneur producing instant chili sauce and has utilized the Shopee e-commerce platform since 2016. However, amidst the increasing trend of chili sauce consumption, this brand faces challenges in optimizing digital marketing and intense competition. This study aims to formulate an optimal digital marketing strategy to improve Sambal Bu Sandra's sales performance on Shopee. The method used is a SWOT analysis, which includes the preparation of IFAS and EFAS matrices to identify strengths, weaknesses, opportunities, and threats. The analysis results show that the business is in quadrant I in the IE matrix, which reflects strong internal conditions and significant external opportunities. The resulting strategies include collaborative product development, optimization of Shopee features (such as Shopee Live and Shopee Ads), digital campaigns based on customer reviews, and adoption of a pre-order system. This study concludes that SWOT integration can provide strategic recommendations based on actual business conditions, which, if applied consistently, can potentially strengthen the brand's position in a competitive digital market.